Studi Fenomenologi Dampak Psikologis Anak Selama Belajar Dirumah Akibat Pandemi Covid-19 - Wati, Del Fatma; Jafone, Fegi Ami; Amelia, Sherly (REAL in Nursing Journal, 2021)
Background: The world is troubled by the outbreak of the corona virus disease (Covid-19) which has become a pandemic. There are many countries have to close schools and ask the students learn from home. The psychological impact of learning from home are anxiety, fear, excessive worry and impacts on psychosocial and other disorders. Methods: The type of this research was qualitative research methods with phenomenological approachon 6 participants. They were consisted to 4 girlsand 2 boys in the age range 9-12 years. They had been selected by purposive sampling technique.The data were collected through in-depth interviews.Then, it was analyzed by Colaizzi method. Results: The results of the interview obtained 5 themes, namely 1) Response to the Covid-19 pandemic, 2) Inability to complete school work, 3) Personal independence not achieved, 4) Loss of group roles, 5) Inability to understand information received. Conclusion: It can be concluded that while learning from home, children had psychological development that deviates from their normal ages. It is recommended to the government, health workers, parents provide psychological support to children while learning from home.Keywords: Pandemic Covid-19, Psychological Impact, Learning from Home